Effect of Current Density, Surfactants, and CuSO4 Concentration on Copper Electroplating of Iron Surfaces - Anisa Fatma Aulia; Nurul Faizah; Gladys Sukma Thufailah (Institut Teknologi Sepuluh Nopember, 2026)
Corrosion poses a serious threat to various industries, leading to financial burdens and infrastructure deterioration. This research investigates the influence of current density, surfactants, and CuSO₄ concentration on the electroplating process of copper onto iron surfaces. Current densities of 0.069825, 0.078069, 0.082062, 0.096939, and 0.129863 A in⁻², boric acid surfactant concentrations of 0.6, 0.9, 1.2, 1.5, and 1.8 g, and CuSO₄ concentrations of 0.40, 0.45, 0.50, 0.55, and 0.60 N were analyzed to assess their effects on the quality of the deposited copper layer. For each condition the deposited layer was evaluated through changes in specimen thickness and mass and through an extrapolated corrosion rate (mils per year, mpy) of the copper anode. Increasing current generally raised the amount of deposited copper, but the relationship with thickness, mass, and corrosion rate was non-monotonic rather than strictly increasing, indicating that current alone does not control coating quality. Adding boric acid buffer promoted a smoother deposit and, at the highest addition (1.8 g), coincided with the lowest measured anodic corrosion rate; excessive amounts, however, are undesirable on adhesion and toxicity grounds. Within the range tested, a moderate CuSO₄ concentration gave the most uniform deposition. Because corrosion rates were extrapolated to an annual basis from very short (5 min) tests, the absolute mpy values should be read as relative comparisons only. The results underline the need to tune, rather than simply maximise, electroplating parameters to obtain a high-quality copper coating on iron.